PERBANDINGAN PENGUNGGUNAAN PUPUK KIMIA DAN NUTRISI UNTUK TANAMAN PADI TERHADAP HARGA POKOK PRODUK DI DESA PAPUNGAN - Lailatul Cahya Ningsih; Istantyo Yuwono (LPPM Universitas Bina Bangsa, 2023)
In 2022 the government in Blitar Regency reduces the amount of subsidized chemical fertilizers again, this has been done for several years by the central government. The main goal is to replace chemical fertilizers with organic fertilizers. However, the lack of government assistance for the use of organic fertilizers causes farmers to suffer losses due to crop failure or crop yields that are far from expectations. This causes the cost of rice production to increase while the quality and weight decrease. The farmer movement in Papungan Village has created a nutritional formula that can replace chemical fertilizers without reducing crop quality and also requires a large amount of money to make these nutrients. This study uses the full costing method which calculates all the cost elements incurred by farmers who use chemical fertilizers and those who use nutrients. Then see if there is an average growth equation if the two are compared using the T-Test method. The results obtained from the calculation of the cost of production can be used as a reference for farmers to switch to nutrition and not rely on chemical fertilizers whose prices have skyrocketed